2019
DOI: 10.3390/min9120737
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Ligand Microstructure of Arsenopyrite from Gold Ore Deposits of the Yenisei Ridge (Eastern Siberia, Russia)

Abstract: The Mössbauer spectroscopy method was used to study the ligand microstructure of natural arsenopyrite (31 specimens) from the ores of the major gold deposits of the Yenisei Ridge (Eastern Siberia, Russia). Arsenopyrite and native gold are paragenetic minerals in the ore; meanwhile, arsenopyrite is frequently a gold carrier. We detected iron positions with variable distribution of sulfur and arsenic anions at the vertexes of the coordination octahedron {6S}, {5S1As}, {4S2As}, {3S3As}, {2S4As}, {1S5As}, {6As} in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Isomer shifts (IS) are given relative to α-iron at room temperature. Probabilities P of quadrupole splitting P(QS) and magnetic hyperfine fields P(H) were first determined from the experimental spectra and were used to generate a model spectrum and then to fit the results by varying the complete set of parameters [54].…”
Section: Characterizationmentioning
confidence: 99%
“…Isomer shifts (IS) are given relative to α-iron at room temperature. Probabilities P of quadrupole splitting P(QS) and magnetic hyperfine fields P(H) were first determined from the experimental spectra and were used to generate a model spectrum and then to fit the results by varying the complete set of parameters [54].…”
Section: Characterizationmentioning
confidence: 99%
“…The share of such gold can reach 40-60%, and its extraction is carried out by JSC Polyus Krasnoyarsk using its own bio-oxidation technology BIONORD ® [36]. "Invisible" gold is confined to sulfide minerals of the deposit, first of all, to needle-like arsenopyrite of the early association, in which its concentrations range from 0.0n to 2298 ppm [37,38]. According to modern ideas, "invisible" gold in arsenopyrite is present in the form of nanosized Au 0 inclusions and in a structurally bound form [38][39][40].…”
Section: Primary (Hypogene) Sulfide Orementioning
confidence: 99%
“…"Invisible" gold is confined to sulfide minerals of the deposit, first of all, to needle-like arsenopyrite of the early association, in which its concentrations range from 0.0n to 2298 ppm [37,38]. According to modern ideas, "invisible" gold in arsenopyrite is present in the form of nanosized Au 0 inclusions and in a structurally bound form [38][39][40]. Earlier Mössbauer studies on 197 Au atoms for gold-bearing arsenopyrite of the Olympiada deposit showed that the content of structurally bound and nanosized metallic gold varies between 3 and 45% and 55 and 97%, respectively [37].…”
Section: Primary (Hypogene) Sulfide Orementioning
confidence: 99%
“…The third part of the issue contains two articles on Au-bearing arsenopyrite and pyrite [17,18]. A significant number of studies are devoted to Au and other noble metals in these minerals.…”
mentioning
confidence: 99%
“…Sazonov and coauthors [17] used the Mössbauer spectroscopy method to study the ligand microstructure of natural arsenopyrites from the ores of major gold deposits of the Yenisei Ridge (Eastern Siberia, Russia). The elevated gold concentrations typical of arsenopyrites occur with an elevated content of sulfur or arsenic and correlate with the increase in the occupation degree of configurations {5S1As}, {4S2As}, {1S5As}, the reduction in the share of {3S3As}, and the amount of iron in tetrahedral cavities.…”
mentioning
confidence: 99%